Photoelectron diffraction, multi-atom resonant photoemission, pioneered by Fadley - Fujikawa, T.; Niki, K.; Kogo, J. (Journal of electron spectroscopy and related phenomena, 2022)
We discuss two important subjects pioneered by Fadley. As the first topic, we discuss the energy dependence of the intensity ratio observed in Mn 3s multiplet splitting excited from antiferromagnetic MnO, MnF2 and KMnF3. We apply the many-body scattering theory developed by Hedin in order to incorporate the extrinsic effects. We find that the extrinsic effects play an important role to explain the energy dependence of the branching ratio. Preliminary calculations show the smaller energy dependence than that observed. As the second topic we briefly discuss some features in multi-atom resonant photoemission (MARPE) based on the first principle quantum theory. Importance of the local symmetry around an emitter is stressed. •We discuss two important subjects pioneered by Fadley.•As the first topic, we discuss the energy dependence ofthe intensity ratio observed in Mn 3s multiplet splitting excited from antiferromagnetic MnO, MnF2 and KMnF3.•We apply the many-body scattering theory developed by Hedin in order to incorporate the extrinsic effects.